2017
DOI: 10.18632/oncotarget.18983
|View full text |Cite
|
Sign up to set email alerts
|

Daurinol blocks breast and lung cancer metastasis and development by inhibition of focal adhesion kinase (FAK)

Abstract: FAK overexpression has been reported in diverse primary and metastatic tumor tissues, supporting its pro-tumorigenic and pro-metastatic roles. Therefore, we have developed a neo-treatment strategy using daurinol to effectively treat cancer metastasis. Daurinol blocked cancer cell migration and invasion in vitro and exhibited anti-metastatic activity in an experimental metastasis model of breast and lung cancer. Daurinol selectively inhibited phosphorylation of FAK at Tyr925, Tyr576/577, and Tyr397 sites in a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 63 publications
(57 reference statements)
0
5
0
Order By: Relevance
“…Earlier findings showed that FAK is responsible for coordination of cell motility and ECM remodeling during cancer cell invasion, and contributes to the secretion of matrix metalloproteinases [20]. The pharmacological inhibition of FAK phosphorylation was linked to reduced MMP-2 and MMP-9 expression and activation in breast and lung cancer cells [56]. Moreover, FAK was found to be crucial in promoting invasion and matrix metalloproteinases production in GBM [57,58].…”
Section: Discussionmentioning
confidence: 94%
“…Earlier findings showed that FAK is responsible for coordination of cell motility and ECM remodeling during cancer cell invasion, and contributes to the secretion of matrix metalloproteinases [20]. The pharmacological inhibition of FAK phosphorylation was linked to reduced MMP-2 and MMP-9 expression and activation in breast and lung cancer cells [56]. Moreover, FAK was found to be crucial in promoting invasion and matrix metalloproteinases production in GBM [57,58].…”
Section: Discussionmentioning
confidence: 94%
“…The pathway of focal adhesion has been extensively reported to be the most significant pathway in various diseases and signaling pathways as well. It regulates diverse cellular functions that were once activated by focal adhesion kinase (FAK), including adhesion, proliferation, migration, and survival [ 38 40 ]. A pattern of enhanced expression of FAK in lung carcinomas has been reported, which is related to nodal involvement and the deterioration of advanced disease stages [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Daurinol (3) decreased the expression of focal adhesion kinase, which is hyper-activated and overexpressed in most solid tumors, but did not block the AKT pathway in both cell lines. Using a trans-well assay, daurinol (3) was found to inhibit migration and invasion (Woo et al 2017).…”
Section: Cytotoxic Activitiesmentioning
confidence: 99%